Deciphering work environment impacts on organizational citizenship behavior: The mediating role of job satisfaction in Ghana's tourism industry - Obeng, Hayford Asare; Arhinful, Richard; Mensah, Leviticus; Gyamfi, Bright Akwasi (International Journal of Innovative Research and Scientific Studies, 2025)
This study aims to examine the mediating role of job satisfaction in the relationship between the work environment and organizational citizenship behavior within the Ghana tourism industry, utilizing the Job Demands-Resources paradigm to explore these relationships. Data from 361 individuals were obtained via online surveys disseminated using Google Forms, employing convenience sampling. The data were analyzed using the Structural Equation Modeling (SEM) methodology to examine the direct and indirect correlations among the variables in AMOS version 23. The results show that the work environment has a significant and positive influence on job satisfaction and organizational citizenship behavior. Furthermore, a significant positive relationship exists between job satisfaction and organizational citizenship behavior. The study discovered that job satisfaction partially mediates the relationship between the work environment and organizational citizenship behavior. The study's findings have significant real-world ramifications for Ghana's tourism sector.